Evaluation of the Health Information System in Teladan Public Health Center in 2020 Using the Health Metrics Network Instrument Approach - Anggun Hasanah; Delia Nurrahmah Rangkuti; Gisa Zel Dita Pinem; Fauziah Nasution (International Archives of Medical Sciences and Public Health, 2021)
The Health Information System is an integrated system that systematicallymanages public data and information (Government, community and private) atall levels of government to support health development in a health facility.This description can be known by conducting a Health Information System(HIS) evaluation activity. This study aims to determine the description of thehealth information system at the Teladan Health Center in Medan City. Theresearch was conducted at the Medan City Teladan Public Health Center,North Sumatra, in June 2019. The subject in this study was the Head of theAdministrative Subdivision of the Teladan Public Health Center, which wastaken based on purposive sampling. The data were gathered through directinterviews and observations. We are using the triangulation method todetermine the data's validity. With a percentage of 73%, health informationsystem resources are classified as "adequate."This is because the Utilizationand Dissemination component is included in the adequate category (63%); thisis because the public health centres have implemented health informationsystems based on the latest Law and are carried out in full and regularly. Theoverall Data Source component is included in the adequate category (64%).Evaluation of Indicator components is included in the very adequate category(78%). The performance evaluation of the health information system at theMedan City Model Health Center was carried out using the Health MetricsNetwork (HMN) version 4.0 instrument approach by assessing variouscomponents of the health information system. According to the evaluationresults conducted at the Teladan Public Health Center, only one of the sixHIS components scored "adequate" on the HMN instrument, with the highestscore on the Indicator Component and the lowest score on the InformationProduct Component.